2016
DOI: 10.1111/jspn.12165
|View full text |Cite
|
Sign up to set email alerts
|

Rehospitalization of preterm infants according to the discharge risk level

Abstract: Nurses can help to minimize rehospitalization of infants by parental education, telephonic counseling, frequent observation, and home care support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“… 6 29 Such high rates, however, show a similar trend from previous studies. 30 On the one hand, this notifies paediatricians and caregivers of a high probability of morbidities within the first months caring at home. On the other hand, this raises concerns about discharge planning as well as a broad indication for hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
“… 6 29 Such high rates, however, show a similar trend from previous studies. 30 On the one hand, this notifies paediatricians and caregivers of a high probability of morbidities within the first months caring at home. On the other hand, this raises concerns about discharge planning as well as a broad indication for hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Aykanat Girgin and Cimete [17] described the causes for re-hospitalization in about 100 preterm infants within 8 weeks after NICU discharge and reported that “medical problems,” including pneumonia, urinary tract infection, jaundice, sepsis/meningitis, anemia, dehydration, or milk allergy were the etiology for re-hospitalization among 68% of their population, and surgical diagnoses, including hernias, repair of retinopathy, and shunt implantation, were the etiology in 23%. Á Rogvi et al [10] used the Danish patient registry for hospital admission to characterize the etiology of re-hospitalization in preterm or small for gestational age infants compared to full-term infants.…”
Section: Discussionmentioning
confidence: 99%
“…parents and their child, child abuse and parental anxiety (24,25). Providing accommodation for the mother and her partner and home support during the transition period has been reported to reduce the number of re-hospitalisations and visits to the emergency department (26,27).…”
Section: Accepted Articlementioning
confidence: 99%